Practical enhanced reservoir engineering : assisted with simulation software - Satter, Abdus (Knovel Library., 2008)
"This book is intended to be a reservoir engineering book for college students, but it is not the usual college text book. It is a modern and very practical guide offering reservoir engineering fundamentals, advanced reservoir related topics, reservoir simulation fundamentals, and problems and case studies from around the world. It is designed to aid students and professionals alike in their active and important roles throughout the reservoir life cycle (discovery, delineation, development, production, and abandonment), and in the various phases of the reservoir management process (setting strategy, developing plan, implementing, monitoring, evaluating, and completing)."--Publisher's website.